Sequence of the 20-kilodalton heavy chain peptide from the carboxyl-terminus of bovine cardiac myosin subfragment-1. - I L Flink; E Morkin (The Journal of Clinical Investigation, 1984)
An almost complete amino acid sequence of the carboxyl-terminal 20-kD tryptic heavy chain peptide from bovine cardiac myosin Subfragment-1 (S-1) has been determined by automated sequential degradation of the undigested peptide and subfragments derived by chemical and enzymatic digestion. The fragment contains 169 residues, including two reactive cysteinyl residues which are located nine residues apart. At six positions in the sequence, two amino acid residues were present and two different versions of a chymotryptic peptide were isolated in approximately 53 and 24% yields, suggesting that there are two cardiac myosin beta-type heavy chains in this species. Analysis of the secondary structure of the 20-kD peptide predicts that there are two distinct regions within the fragment. The first region (residues 1-121) contains 12% alpha-helix, 25% beta-sheet, 40% beta-bends, and 19% coil; the second region (residues 122-169) may form an extended alpha-helix. Comparison of the bovine sequence with the deduced amino acid sequence of a recombinant plasmid containing DNA sequences coding for the beta-heavy chain of rabbit cardiac myosin (pMHC beta 174) reveals approximately 86% homology. Images